Inferior Vena Cava Volume Is an Independent Predictor of Massive Transfusion in Patients With Trauma. (April 2021) - Chien, Chih-Ying; Yan, Jiun-Lin; Han, Shih Tsung; Chen, Jin-Tang; Huang, Ting-Shuo; Chen, Yu-Hsien; Wang, Chih-Yuan; Lee, Yueh-Lin; Chen, Kuan-Fu
Objectives: Early adequate resuscitation of patients with trauma is crucial in preventing shock and early mortality. Thus, we aimed to determine the performance of the inferior vena cava (IVC) volume and other risk factors and scores in predicting massive transfusion and mortality. Methods: We included all patients with trauma who underwent computed tomography (CT) scan of the torso, which included the abdominal area, in our emergency department (ED) from January 2014 to January 2017. We calculated the 3-dimensional IVC volume from the left renal vein to the IVC bifurcation. The primary outcome was the performance of IVC volume in predicting massive transfusion, and the secondary outcome was the performance of IVC volume in predicting 24-hour and 30-day in-hospital mortality. Results: Among the 236 patients with trauma, 7.6% received massive transfusions. The IVC volume and revised trauma score (RTS) were independent predictors of massive transfusion (adjusted odds ratio [OR]: 0.79 vs 1.86, 95% confidence interval [CI], 0.71-0.89 vs 1.4-2.47, respectively). Both parameters showed the good area under the curve (AUC) for the prediction of massive transfusion (adjusted AUC: 0.83 and 0.82, 95% CI, 0.74-0.92 vs 0.72-0.93, respectively). Patients with a large IVC volume (fourth quartile) were less likely to receive massive transfusion than those with a small IVC volume (first quartile, ≥28.29 mL: 0% vs <15.08 mL: 20.3%, OR: 0.13, 95% CI, 0.03-0.66). Conclusions: The volume of IVC measured on CT scan and RTS are independent predictors of massive transfusion in patients with trauma in the ED.